The Mechanical Role of the Surface of Articular Cartilage - Wu, Jianping; Teo, S.; Kirk, Thomas Brett (ISB Technical group on computer simulation, 2011)
Articular cartilage has remarkable biomechanical properties that permit transmitting loads, attenuating dynamic stresses and almost frictionless movements without causing joint pain [1]. Its surface stands for various compressive, shearing and wearing stresses. Disruption of the surface occurs during accidents and physical activities. It consequently leads to the development of osteoarthritis. In this study, the internal microstructure and mechanical function of normal cartilage and the cartilage with the surface disruption have been examined. The chondrocyte shape and mechanical properties of articular cartilage have been found to be altered due to the disruption of the surface.